(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1997)
In the present paper, the concept of logistics is used to construct a decision making system for choosing the best logistics chain. In principle, the logistic approach to the management of material flows differs from the conventional one in following: it integrates separate elements into the common system that is able to react adequately to the perturbation of the environment (Coyle, Bardi et al. 1992).Logistics operations on the way of material flow movement from the initial source of raw materials to the terminal consumer are mostly fulfilled by using various transport vehicles. Costs for performing these operations constitute 50% of the total amount of logistics costs.Logistics chain is a linearly ordered set of participants of the logistic process that implement logistics operations on transportation of the external material flow from one logistics system to another (see Figure. 1).The presence of an uncertain decision making situation, probabilistic data changing as the time changes, complex relationships among the variables and the subjectivity of task perception in the given problem make it necessary to use an influence diagram (Moravski 1989) as a model of decision making problem.